Mejora al proceso "Servicio de atención al ciudadano y al operador" en el Ministerio de Tecnologías de la Información y las Comunicaciones (2011)
Technological breakthroughs determine how people communicate with one other, which has led to the emergence of a knowledge society; in Colombia, the ministerial office of Information and Communications Technology, promotes the use of ICT on equal terms to all citizens. This research focuses on the process of Petitions, Complaints and Grievances, in order to formulate and implement a systematic series of actions which are integrated among themselves understandable to strengthen the opportunity of caring for requests and complaints to the requested entity.The project included both design and partial implementation of the improvement proposal inside the entity with emphasis on: the definition of the new route for the attention of requests, complaints and claims, the development of guidelines for the use of new communication channels defined by the ministerial office of ICT, the updating of procedures including the reallocation of roles and responsibilities, awareness of staff involved in customer service activities, development of management tools and the continuous strengthening of the commitment of the top management in the redesign process.According to all above, the improvement proposal formulated by the research team constitutes the impulse motor and reference point for the redesigns of the costumer and operator suppot within the ministerial office of ICT, an action which is actually under development and will count with the support of one of the members of the research team who works for the entity and has been appointed member of the team leading the redesign of this important process.